Polymeric superabsorbent hydrogel-based kinetic promotion for gas hydrate formation. (15th March 2021) - Sun, Meng-Ting; Song, Fu-Peng; Zhang, Guo-Dong; Li, Jing-Zhe; Wang, Fei
Abstract: Gas hydrates hold great potential in the field of energy storage & transportation. However, the stochastic induction time and low formation rate restricted the large-scale industrialization of gas hydrate technology, which need to be improved through effective methods. Superabsorbent hydrogels (SAHs) are lightly cross-linked polymers with three-dimensional networks that can absorb and retain a large amount of water or aqueous solution. Due to the strong absorption and retention capabilities, SAHs have been added in the system to facilitate gas hydrate formation via increasing mass transfer and improving promoter recyclability. However, the interactions among gas, water and hydrogels are complicated, and the usages are diverse, and the promotion mechanisms were underexplored. This paper reviews the existing cases applying SAHs in gas hydrate formation, and analyzes the influencing mechanisms of SAHs; and meanwhile proposes a concept of SAH-based solid-state water (SSW) system, and evaluates its application potential in promoting gas hydrate formation, and further prospects its modification and integration possibilities for being a hydrate promoter.